Somatic mutations and affinity maturation are impaired by excessive numbers of T follicular helper cells and restored by Treg cells or memory T cells. Issue 11 (1st October 2015) - Preite, Silvia; Baumjohann, Dirk; Foglierini, Mathilde; Basso, Camilla; Ronchi, Francesca; Rodriguez, Blanca M. Fernandez; Corti, Davide; Lanzavecchia, Antonio; Sallusto, Federica
Abstract : We previously reported that Cd3e ‐deficient mice adoptively transferred with CD4 + T cells generate high numbers of T follicular helper (Tfh) cells, which go on to induce a strong B‐cell and germinal center (GC) reaction. Here, we show that in this system, GC B cells display an altered distribution between the dark and light zones, and express low levels of activation‐induced cytidine deaminase. Furthermore, GC B cells from Cd3e –/– mice accumulate fewer somatic mutations as compared with GC B cells from wild‐type mice, and exhibit impaired affinity maturation and reduced differentiation into long‐lived plasma cells. Reconstitution of Cd3e –/– mice with regulatory T (Treg) cells restored Tfh‐cell numbers, GC B‐cell numbers and B‐cell distribution within dark and light zones, and the rate of antibody somatic mutations. Tfh‐cell numbers and GC B‐cell numbers and dynamics were also restored by pre‐reconstitution of Cd3e –/– mice with Cxcr5 –/– Treg cells or non‐regulatory, memory CD4 + T cells. Taken together, these findings underline the importance of a quantitatively regulated Tfh‐cell response for an efficient and long‐lasting serological response.